2013
DOI: 10.2174/157015913804999441
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for Investigating Benign Essential Blepharospasm

Abstract: The focal dystonia benign essential blepharospasm (BEB) affects as many as 40,000 individuals in the United States. This dystonia is characterized by trigeminal hyperexcitability, photophobia, and most disabling of the symptoms, involuntary spasms of lid closure that can produce functional blindness. Like many focal dystonias, BEB appears to develop from the interaction between a predisposing condition and an environmental trigger. The primary treatment for blepharospasm is to weaken the eyelid-closing orbicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…MS was also found to be associated with decreased inhibition in the cerebral cortex caused by environmental factors and genetic susceptibility ( 9 , 14 , 40 ). Animal studies have demonstrated that abnormal interactions among trigeminal blink circuits, basal ganglia, and the cerebellum contribute to the disease ( 41 ). Although there is no definitive evidence for the existence of MS susceptibility genes, some studies indicate that it is a low penetrance autosomal dominant disorder ( 33 , 42 45 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…MS was also found to be associated with decreased inhibition in the cerebral cortex caused by environmental factors and genetic susceptibility ( 9 , 14 , 40 ). Animal studies have demonstrated that abnormal interactions among trigeminal blink circuits, basal ganglia, and the cerebellum contribute to the disease ( 41 ). Although there is no definitive evidence for the existence of MS susceptibility genes, some studies indicate that it is a low penetrance autosomal dominant disorder ( 33 , 42 45 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…An animal model of BSP has been reported in which a 6-hidroxi-dopamine lesion of the striatum together with a peripheral nerve lesion may lead to enhanced reflex gain ( 54 , 55 ). This may apply to humans with some predisposition to develop dystonia, where unilateral peripheral facial nerve lesions lead to enhancement of blink reflex excitability recovery in the side contralateral to paresis.…”
Section: Review Of Known Bsp Phenomenologymentioning
confidence: 99%
“…This may be interpreted as changes in neurotransmitter (NT) production, NT transmission, and NT receptor functions as age increases. In previous animal model, having both depleting the dopamine NT and eye irritation condition produce the BSP, and cerebellum blocked blink amplitude and duration (Evinger, 2013 ; Hall et al., 2006 ). It can be interpreted that NT depletion according to age can contribute to the etiology of BSP.…”
Section: Discussionmentioning
confidence: 98%